Illegal medicinal purposes advertisement in Malaysia with reference to the medicine (advertisement and sale) act 1956 / Stefheni Zoes Maiks, Siti Salwa Mohd Yunos - Zoes Maiks, Stefheni; Mohd Yunos, Siti Salwa (2007)
This research aims to analyse and determine the legality of medicinal purposes advertisements that are publicise in Malaysia and to examine into the reasons and effects of the non-compliance with the law that govern these type of advertisement. The illegal medicinal purposes advertisement is basically those advertisements that does not complied with the requirements under the main governing law which is the Medicine (Advertisement and Sale) Act 1956. This Act falls under the custody of Medicine Advertisement Board from the Pharmaceutical Service Division of the Ministry of Health. Besides the major Act which govern this matter, the existence of others statutory authorities, bodies and organizations who are also accountable in curbing the existence of the illegal medicinal purposes advertisement are also been discussed thoroughly in this research in order to make the law more effective and enforceable.